Steel for machine construction with excellent grain size characteristics

JP7653277B2Active Publication Date: 2025-03-28SANYO SPECIAL STEEL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021049761
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-24
Publication Date
2025-03-28
Estimated Expiration
2041-03-24

Smart Images

  • Figure 0007653277000001
    Figure 0007653277000001
  • Figure 0007653277000002
    Figure 0007653277000002
Patent Text Reader

Abstract

To provide a steel for mechanical structures that can inhibit the coarsening of crystal grains during carburization.SOLUTION: A steel for mechanical structures having excellent grain size properties comprises, in mass%, C: 0.27-0.45%, Si: 0.1-0.9%, Mn: 0.1-0.6%, P (as unavoidable impurities): 0.030% or less, S (as unavoidable impurities): 0.030% or less, Cr: 1.50-2.50%, Mo: 0.1-0.3%, Al: 0.005-0.050%, N: 0.004-0.030%, with the balance being Fe and inevitable impurities. The steel is in an annealed state. The area ratio of lamellar pearlite is 3% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel for machine structure use that is suitable as a material for parts that are used after being subjected to surface hardening treatment such as carburizing, carbonitriding, or nitriding after hot forging, such as gears, CVJs, and shafts for automobiles, construction machinery, machine tools, etc. [Background technology]

[0002] Steels for machine and structural use suitable for the above applications have been proposed so far. The applicant has proposed an invention for a steel for machine construction that has superior grain size resistance compared to conventional carburizing steels, regardless of whether it has been hot worked or cold worked, or whether it has been normalized before carburizing, by optimizing the steel composition and specifying the grain size of the ferrite, pearlite, and bainite structures before carburizing (see Patent Document 1). This steel is designed to have a ferrite or ferrite-pearlite structure containing bainite before carburizing.

[0003] In addition, in order to prevent coarse grains, an invention has been proposed for a case-hardened steel with excellent fatigue properties, which is achieved by controlling the amount of MnS produced by utilizing Ti-based carbosulfides or optimizing the Ti and S contents (see Patent Document 2).

[0004] Furthermore, in order to prevent coarse grains, inventions have been proposed for case-hardened steels that can suppress the generation of abnormal grains during carburizing treatment by utilizing carbonitrides of Ti and Nb, or by optimizing the Ti and Nb contents, and by specifying the size and number density of these carbonitrides (see Patent Documents 3 and 4).

[0005] These proposals for steels for mechanical construction are based on the premise that the pre-carburizing structure is a ferrite-pearlite structure containing bainite, or involve the prevention of grain coarsening by utilizing the pinning effect of precipitates. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2017-106079 A [Patent Document 2] JP 2017-133052 A [Patent Document 3] JP 2015-160979 A [Patent Document 4] JP 2014-101566 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, in recent years, carburizing conditions have become higher in temperature, and conventionally proposed steels are insufficient, and crystal grains may become coarse in some areas.

[0008] Furthermore, in the case of carburized parts, medium carbon steels containing Mo, such as SCM435, are sometimes used to ensure core hardness in large parts, increase the strength of parts, and shorten the carburizing time. However, even in these cases, the structure before carburizing tends to become a ferrite-pearlite structure containing bainite, which can easily cause grain coarsening during carburizing.

[0009] Furthermore, even if the cooling rate is controlled to control the bainite, the grains may become coarse.

[0010] Therefore, in consideration of the background when carburizing steel for machine structural use, an object of the present invention is to provide a steel for machine structural use that can suppress grain coarsening during carburization.

[0011] In general, in order to suppress the coarsening of crystal grains during carburizing, normalizing is applied after hot forging, and the structure before carburizing is often a two-phase structure of ferrite + austenite. However, this normalized structure is prone to have non-uniform distribution of globular carbides after slow cooling due to the process of maintaining the structure in the two-phase region of ferrite + austenite. Such non-uniformity of carbide distribution is one of the causes of grain coarsening in the subsequent carburizing process, so it is desirable to make the carbide distribution uniform. [Means for solving the problem]

[0012] Therefore, as a result of intensive research, the inventors have decided in the present invention to disperse nano-order fine precipitates (Al nitrides, Nb carbonitrides, Fe carbides, Cr carbides, etc.) in the ferrite after hot forging by adjusting the steel composition. After hot forging, a mixed phase structure of ferrite, pearlite, or bainite is formed, and during the cooling process after hot forging (below the A1 point temperature), spherical carbides precipitate in the ferrite grains with the above-mentioned fine precipitates as nuclei. By applying annealing in such a dispersed state of spherical carbides, the spheroidization of the carbides constituting the pearlite and bainite is promoted.

[0013] As a result, it was discovered that in medium carbon steel containing Mo, spherical carbides are uniformly dispersed within the ferrite grains, resulting in an excellent steel that can simultaneously ensure core hardness in large products, increase the strength of parts, shorten carburization times, and resist grain coarsening during carburization.

[0014] Therefore, a first means for solving the problems of the present invention is a steel for machine structural use having, by mass%, C: 0.27-0.45%, Si: 0.1-0.9%, Mn: 0.1-0.6%, P (as unavoidable impurities): 0.030% or less, S (as unavoidable impurities): 0.030% or less, Cr: 1.50-2.50%, Mo: 0.1-0.3%, Al: 0.005-0.050%, N: 0.004-0.030%, with the balance being Fe and unavoidable impurities, the steel being in an annealed state and having an area ratio of lamellar pearlite of 3% or less, and having excellent crystal grain size characteristics.

[0015] The second means is a steel for mechanical structural use having, in addition to the chemical components described in the first means, by mass%, Nb: 0.10% or less, Ti: 0.020 to 0.200%, B: 0.0030% or less, with the balance being Fe and unavoidable impurities, and the steel is in an annealed state and has an area ratio of lamellar pearlite of 3% or less, and has excellent crystal grain size characteristics.

[0016] The third means is a steel for machine structural use having excellent grain size characteristics, in which a steel consisting of the chemical components as described in the first or second means, the balance being Fe and unavoidable impurities, is carburized and has a core hardness of 550 Hv or more after carburization. Effect of the Invention

[0017] According to the present invention, annealing is applied in a state where spherical carbides are dispersed in ferrite grains, so that a structure in which the spherical carbides are uniformly dispersed and a structure with little lamellar pearlite, with an area ratio of lamellar pearlite of 3% or less, can be obtained. When a steel having the chemical composition specified in the present invention and an area ratio of lamellar pearlite of 3% or less is selected in an annealed state, it becomes a steel for machine construction with excellent grain coarsening resistance, with a Rockwell hardness of 90HRB or less and a grain size number of 8 or more after annealing. Furthermore, according to the present invention, the steel has a core hardness of 550Hv or more after pseudo-carburization. Therefore, when the steel according to the present invention is carburized, a steel for machine structural use in which the grain coarsening characteristics are suppressed is obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Before describing the embodiment of the present invention, the reasons for specifying the chemical composition of the steel in the present invention and the reasons for limiting the area ratio of lamellar pearlite after annealing of the steel will be described. Note that % in the following chemical compositions is mass %.

[0019] C: 0.27-0.45% C is an element necessary for maintaining the core hardness of steel parts after carburization and imparting strength. However, if C is less than 0.27%, the core hardness of the steel parts after carburization decreases, resulting in insufficient strength. On the other hand, if C is more than 0.45%, the material hardness increases, and machinability and cold workability decrease. Therefore, C is set to 0.27 to 0.45%. Preferably, C is 0.27 to 0.43%.

[0020] Silicon: 0.1 to 0.9% Silicon is an effective element for deoxidation during steelmaking. However, if the silicon content is less than 0.1%, it is easy for insufficient deoxidation during steelmaking to occur, resulting in a decrease in the inclusion quality. On the other hand, if the silicon content is more than 0.9%, the material hardness increases, workability decreases, and carburization inhibition occurs. Therefore, the silicon content is set to 0.1 to 0.9%.

[0021] Mn: 0.1-0.6% Mn is an element that improves the hardenability of steel, but if the content is less than 0.1%, the hardenability is insufficient, while if the content is more than 0.6%, the workability is reduced. Therefore, the Mn content is set to 0.1 to 0.6%.

[0022] P (as unavoidable impurities): 0.030% or less P is contained as an inevitable impurity. However, if the P content is more than 0.030%, it promotes grain boundary segregation and reduces toughness. Therefore, the P content is set to 0.030% or less as an inevitable impurity.

[0023] S (as unavoidable impurities): 0.030% or less S is contained as an inevitable impurity. However, if the S content is more than 0.030%, a large amount of coarse MnS is formed, which reduces the toughness and fatigue strength. Therefore, the S content as an inevitable impurity is set to 0.030% or less.

[0024] Cr: 1.50~2.50% Cr is an element effective in improving the hardenability, toughness, and temper softening resistance of steel. However, if Cr is less than 1.50%, the A1 point does not rise enough, so the lamellar pearlite ratio increases and the crystal grains become coarse. In addition, hardenability is insufficient. On the other hand, if Cr is more than 2.50%, the material hardness increases and workability decreases. In addition, the risk of carburization inhibition increases. Therefore, the area ratio of Cr lamellar pearlite is set to 1.50-2.50% so that it is 3% or less. Preferably, Cr is 1.60-2.50%.

[0025] Mo: 0.1-0.3% Mo is an element that is effective in increasing the hardness of the material. However, if the Mo content is less than 0.1%, the core hardness after carburization decreases, resulting in insufficient strength. On the other hand, if the Mo content is 0.3% or more, the material hardness increases too much, decreasing workability, resulting in poor machinability and cold workability. Therefore, the Mo content is set to 0.1 to 0.3%.

[0026] Al: 0.005 to 0.050% Al is an effective element for deoxidizing steel, and reacts with N in steel to form AlN. However, if Al is less than 0.005%, deoxidation during manufacturing is likely to be insufficient, resulting in a decrease in the inclusion quality. In addition, fine nitrides are insufficient, and crystal grains tend to become coarse, resulting in a decrease in toughness and fatigue properties. On the other hand, if Al is more than 0.050%, the formation of coarse nitrides (AlN) leads to a decrease in fatigue properties and workability. Therefore, Al is set to 0.005 to 0.050%.

[0027] N: 0.004~0.030% N is an element that reacts with Al in steel to form AlN. However, if the N content is less than 0.004%, the fine carbonitrides are insufficient, resulting in coarsening of crystal grains and a decrease in toughness and fatigue properties. On the other hand, if the N content is more than 0.030%, the fatigue properties and workability decrease due to the formation of coarse carbonitrides. Therefore, the N content is set to 0.004 to 0.030%.

[0028] The above is the reason why the essential elements to be added to Fe in the steel of the present invention are specified. Next, the optional elements will be explained.

[0029] Nb: 0.10% or less Nb is an element that forms fine carbonitrides, so it is an effective component for improving grain coarsening resistance. However, if the Nb content is more than 0.10%, the number of coarse carbonitrides increases, and the grains become coarse due to the decrease in the carbonitrides that have a pinning effect. Therefore, when Nb is added, it is set to 0.10% or less.

[0030] Ti: 0.020~0.200% Ti is an element that forms fine nitrides, so it can be added as desired. However, if Ti is less than 0.020%, the amount of fine nitrides formed is insufficient, and the crystal grains tend to become coarse. In addition, since N is not fixed, BN is formed, and hardenability decreases. On the other hand, if Ti is more than 0.200%, the amount of coarse carbonitrides increases, and the carbonitrides that have a pinning effect decrease, causing the crystal grains to become coarse. When the area ratio of lamellar pearlite is 3% or less and Ti is added, the amount is set to 0.020 to 0.200%.

[0031] B: 0.0030% or less B is an element that contributes to hardenability, and can be added as desired. However, if it is contained in an amount of more than 0.0030%, the material hardness increases, resulting in a decrease in workability. Therefore, the B content is set to 0.0030% or less.

[0032] Lamellar pearlite area ratio: 3% or less If the area ratio of lamellar pearlite after annealing is 3% or less, grain uniformity can be obtained without the occurrence of partial grain coarsening. Therefore, the area ratio of lamellar pearlite is set to 3% or less.

[0033] Next, the mode for carrying out the present invention will be described. First, 100 kg of 33 types of steels, including 16 types of steels A to P of the invention steels and 17 types of steels Q to Z and AA to AG of the comparative steels, each having the chemical components shown in Table 1 with the balance being Fe and unavoidable impurities, were melted in a vacuum melting furnace.

[0034] [Table 1]

[0035] Next, each of these steel specimens was hot forged into a steel bar with a diameter of 40 mm, which was then annealed at a temperature of 700 to 850°C for 1 to 3 hours and then air-cooled. The annealing was performed using a Kanthal furnace according to the following procedure.

[0036] The annealing procedure in the Kanthal furnace is as follows: first, the test material is placed in the furnace set to the holding temperature for spheroidizing annealing, and the test material is allowed to heat up for 30 minutes, then it is held for a desired period of time, and then air-cooled or water-cooled. In this example, air-cooling was used in both cases. The holding time at the austenitizing temperature should be selected taking into consideration the amount and dimensions of the steel material to be charged into the furnace.

[0037] The properties of the annealed steel were confirmed as follows: lamellar pearlite area ratio and hardness after annealing. After annealing, a pseudo-carburizing test was also conducted to confirm the grain size and core hardness. The results are shown in Table 2.

[0038] (Regarding lamellar pearlite area ratio) First, a cross section of about 10 mm square was cut from the forging direction of the steel material, mirror-polished, and then etched with 5% nital. The lamellar pearlite area ratio was calculated by taking a structural image of an 800 μm square with an optical microscope, excluding the area of ​​the bainite part from the total area of ​​the 800 μm square by image analysis, and based on the area of ​​the remaining lamellar pearlite part. If the lamellar pearlite area ratio is 3% or less, granulation can be achieved without partial grain coarsening. Therefore, if the lamellar pearlite area ratio is 3% or less, it is indicated as good with ○ in the lamellar pearlite area ratio column in Table 2, and if the lamellar pearlite area ratio exceeds 3%, it is indicated as poor with × in the lamellar pearlite area ratio column in Table 2.

[0039] (Hardness after annealing) The above annealed test material was cut perpendicular to the rolling direction, the cut surface was flat ground, and then a Rockwell hardness test was performed at the center periphery. If the Rockwell hardness was 90HRB or less, it was marked as good with a circle in the column for hardness after annealing in Table 2, and if the Rockwell hardness was more than 90HRB, it was marked as bad with a cross in the column for hardness after annealing in Table 2.

[0040] Next, after annealing, the steels were subjected to pseudo-carburizing to confirm whether the grain coarsening characteristics were suppressed when these steels were carburized, using the grain size after pseudo-carburizing.

[0041] Quasi-carburizing is a method that gives only the thermal history of carburizing without actually performing carburizing. Generally, carburizing does not directly affect the grain coarsening behavior, so this method makes it possible to appropriately evaluate the grain coarsening temperature. In quasi-carburizing, the temperature was raised at 300℃ / h, which is the assumed heating rate in the general carburizing process, and the material was held at 850℃-970℃ for 5 hours, and then water-cooled.

[0042] (Measuring grain size) The grain size number of the steel was measured and evaluated according to the intercept method of JIS G0551. If the grain size number was 8 or more, it was marked as good in the grain size number column of Table 2 with a circle, and if the grain size number was less than 8, it was marked as poor in the grain size number column of Table 2 with a cross.

[0043] (Core hardness after pseudo-carburizing) The pseudo-carburized test material was cut perpendicular to the rolling direction, and the cut surface was flat ground, after which a Vickers hardness test was carried out at the center position. A Vickers hardness of 550Hv or more was evaluated as good and marked with ◯, whereas a Vickers hardness of less than 550Hv was evaluated as poor and marked with ×.

[0044] [Table 2]

[0045] The invention steels of the steel types A to P, which are the invention steel components, all satisfy the components specified by the invention, and the lamellar pearlite ratio after annealing is 1.3 to 2.7%, which is 3% or less, so that steels without partial grain coarsening are obtained. The hardness of the invention steels A to P after annealing is 81 to 88 HRB, which is 90 HRB or less. In addition, the grain size number of the invention steels A to P after pseudo-carburizing is 8.2 to 9.2, which is 8 or more, so it was confirmed that the grains are not easily coarsened by carburizing. In addition, the invention steels A to P have a core hardness of 566 to 603 HV after pseudo-carburizing, and it was confirmed that the core hardness is 550 HV or more even after carburizing. Since it has the above-mentioned characteristics, the steel for machine structure of the present invention is suitable for parts that are used by performing surface hardening treatment such as carburizing, carbonitriding, and nitriding after hot forging.

[0046] On the other hand, for the steel types Q to AG having comparative steel compositions, when the steel was outside the range specified by the present invention, the following problems were observed: coarsening of crystal grains, deterioration of workability, insufficient core hardness, etc. Steel type Q has an excessive amount of C and a lamellar pearlite ratio of more than 3%, which makes it prone to partial grain coarsening. In addition, the hardness after annealing is too high, which reduces machinability and cold workability, and the grains after pseudo-carburizing are also coarsened. Steel type R has an insufficient amount of C and a lamellar pearlite ratio exceeding 3%, which makes the crystal grains prone to coarsening in some places, and the crystal grains also become coarse after pseudo-carburizing. Steel type S contains too much Si, so the hardness after annealing is too high and the workability is reduced. Steel type T contains too much Mn, so the hardness after annealing is too high and the workability is reduced. Steel type U has an insufficient Cr content, a high lamellar pearlite ratio, and coarse crystal grains. Steel type V contains too much Cr, so the hardness after annealing is too high, resulting in poor workability. Steel type W has an insufficient amount of Mo, so the core hardness after carburization is low and the strength is insufficient. Steel type X contains too much Mo, so the hardness after annealing is too high and the workability is reduced. Since the Al content of steel type Y is too low, fine nitrides are insufficient, and the crystal grains become coarse. Steel type Z contains too much Al, so the hardness after annealing is too high, resulting in poor workability. Steel types AA and AB had N outside the specified range, and coarsening of crystal grains was observed after pseudo-carburizing. Steel type AC contains an excessive amount of Nb, which causes the crystal grains to become coarse. In steel types AD and AE, the Ti content is outside the specified range, causing the crystal grains to become coarse. Steel type AF contains an excessive amount of B, so the hardness after annealing is too high, resulting in poor workability. The lamellar pearlite ratio of steel grade AG is less than 3%, which makes the crystal grains easily coarsen. In addition, the hardness after annealing is too high, which reduces the machinability and cold workability.

Claims

1. A steel for machine structural use having, by mass%, C: 0.27-0.45%, Si: 0.1-0.9%, Mn: 0.1-0.6%, P (as unavoidable impurities): 0.030% or less, S (as unavoidable impurities): 0.030% or less, Cr: 1.50-2.50%, Mo: 0.1-0.3%, Al: 0.005-0.050%, N: 0.004-0.030%, with the balance being Fe and unavoidable impurities, the steel being in an annealed state and having an area ratio of lamellar pearlite of 3% or less, and having excellent crystal grain size characteristics.

2. In addition to the chemical components of claim 1, the following components are contained in the alloy: Nb: 0.10% or less; Ti: 0.020 to 1.0% by mass. 0.200%, B: 0.0030% or less, the balance being Fe and unavoidable impurities. A steel for machine structural use having excellent grain size characteristics, the steel being in an annealed state and having an area ratio of lamellar pearlite of 3% or less.

3. 3. A steel for machine structural use having excellent grain size characteristics, the steel being in a carburized state and comprising the chemical components as set forth in claim 1 or 2 with the balance being Fe and unavoidable impurities, and having a core hardness of 550 Hv or more after carburization.

Citation Information

Patent Citations

  • Steel for high-temperature carburization superior in grain-coarsening resistance, manufacturing method therefor, formed article for high-temperature carburization, and carburizing and quenching method therefor

    JP2006249570A

  • Steel material for machine structural use having excellent contact pressure fatigue strength

    JP2012224928A

  • Method of manufacturing case hardened steel and parts omissible of normalizing after hot-forging and excellent in high temperature carburizability

    JP2014101566A

  • Case-hardening steel in which generation of abnormal grain in carburizing treatment can be suppressed and machine structure component using the same

    JP2015160979A

  • Steel component for high strength high toughness machine structure excellent in pitching resistance and abrasion resistance and manufacturing method therefor

    JP2016050350A